Effect of diminished ovarian reserve on the outcome of fresh embryo transfer in IVF/ICSI cycles among young women: A retrospective cohort study - Suqin Zhu; Wenwen Jiang; Xiuhua Liao; Yan Sun; Xiaojing Chen; Beihong Zheng (BMC, 2024)
Abstract Objective This study aims to investigate the effect of diminished ovarian reserve (DOR) on the clinical outcomes and maternal and infant safety of in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) procedures in young women aged ≤ 35 years. Methods A retrospective cohort study was performed to analyze the clinical data of 4,203 infertile women aged ≤ 35 years who underwent fresh embryo transfer (ET) in IVF/ICSI cycles. The data were collected from their initial visits to Fujian Maternity and Child Health Hospital between January 2015 and January 2022. Based on their ovarian reserve, the participants were categorized into two groups: DOR group (n = 1,027) and non-DOR group (n = 3,176). A propensity score matching (PSM) method was employed to ensure a relatively balanced distribution of covariates. The primary outcome assessed in this study was the live birth rate, while the secondary observation indicators included rates of high-quality embryo development, blastocyst formation, clinical pregnancy, and miscarriage, along with perinatal complications, neonatal birth weight, and the incidence of low birth weight (LBW). Results The DOR group showed notably lowered rates of blastocyst formation (59.8% vs. 64.1%), embryo implantation (29.8% vs.33.3%), clinical pregnancy (47.9% vs. 53.6%), and live birth (40.6% vs. 45.7%) compared to the non-DOR group (all P < 0.05). However, no statistically significant differences were observed in the high-quality embryo rate, miscarriage rate, perinatal complications, neonatal birth weight, or LBW incidence in infants between both groups (all P > 0.05). Conclusion DOR has been found to reduce both clinical pregnancy and live birth rates in young females undergoing fresh ET in IVF/ICSI cycles. However, this reduction does not increase the risk of perinatal complications or LBW of infants through live birth cycles.